2021
DOI: 10.12928/utic.v2.5749.2019
|View full text |Cite
|
Sign up to set email alerts
|

The affective factors influencing students’ speaking ability

Abstract: Considering speaking ability is one of the important abilities that students have to master in learning English. However, most of their speaking ability is low. It is caused by several factors, one of those factors is affective factors (motivation, anxiety, and self-confidence). The research aims to know what affective factors that mostly influence students’ speaking ability. This research applied quantitative design with simple linear regression analysis. The sample of the research is 39 students from two cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Further study conducted by Illyin et al, (2019) affirmed the role of self-confidence and motivation as two affective factors which influence speaking proficiency. Self-confidence is a factor of self-efficacy as it is defined as one's believe towards one's capability to organize and conduct a series of tasks to manage prospective situation(Albert et.al .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Further study conducted by Illyin et al, (2019) affirmed the role of self-confidence and motivation as two affective factors which influence speaking proficiency. Self-confidence is a factor of self-efficacy as it is defined as one's believe towards one's capability to organize and conduct a series of tasks to manage prospective situation(Albert et.al .…”
Section: Discussionmentioning
confidence: 83%
“…Self-confidence is a factor of self-efficacy as it is defined as one's believe towards one's capability to organize and conduct a series of tasks to manage prospective situation(Albert et.al . The study of Illyin et al, (2019) gained significance value as much as 0,007 for self-confidence which means it significantly affected speaking proficiency. In line with this, Ni, (2012) also stated that students with low self-confidence tend to be shy and afraid to express their opinion orally.…”
Section: Discussionmentioning
confidence: 96%
“…Students' motivation is the second most powerful factor in determining their speaking skills; so, if learners are highly motivated, their speaking talents will also be excellent. If learners lack motivation, their speaking abilities will be poor (Illyin et al, 2021). According to the research, students who have confidence have better involvement in things like learning; they have less exam anxiety; they have more interest in goal-setting; and they are more comfortable with their lecturers (Akbari & Sahibzada, 2020).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Another study explained that the cause of anxiety also came from text features on unfamiliar topics (Zayed & Al-Ghamdi, 2019). Another study also elucidated, among the three affective factors on speaking ability of high school students, selfconfidence is the most influential factor, the second is motivation, and anxiety does not affect speaking skills (Illyin et al, 2021). Several studies also show that among junior high school students in China, ordinarily, they suffer from three affective factors, namely anxiety, boredom, and hopelessness (Bao & Liu, 2021;Zhu & Zhou, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that affective factors have prominent roles in EFL, including the significant roles of learning styles, personality traits, low self-confidence, and anxiety among adults (Illyin et al, 2021;Zayed & Al-Ghamdi, 2019). High levels of anxiety are caused by fear of making mistakes, feelings of shame, and lack of confidence.…”
Section: Introductionmentioning
confidence: 99%